Civil Justice, Privatization, and Democracy - TREVOR C.W. FARROW (University of Toronto Press, 2014)
Almost twenty years ago, prior to becoming an academic, I was a litigator in a case that changed my view of the civil justice system. The case involved a dispute over a contract for a computer system and computer services. The parties were located in the United States. The contract provided that any dispute between the parties would be resolved by way of arbitration, which is essentially a trial that is private, funded by the parties and presided over by a neutral person selected by the parties (an arbitrator). The case took several years to prepare, culminating in a week-long hearing. The result, in my view, was a travesty of justice. Fairness was not accomplished, justice was not served, and poor, unethical â€“ and potentially fraudulent â€“ conduct was permitted to persist. Seeing first-hand how a modern private dispute resolution regime could run rough-shod over well-established rule of law values in a case involving informed clients, sophisticated counsel, a senior and experienced lawyer-arbitrator, and important corporate law principles was, put simply, shocking. Although there were potentially several reasons for the unfairness of the result in that case (which, as outlined in Chapter 1, I call the â€œDealership caseâ€), the fact that the dispute was resolved pursuant to a private justice regime, to me, was a root cause of the problem. The procedural safeguards, at least for one party, were not adequate. The problematic conduct at issue in the case, which affected many more people and organizations than those directly involved in the dispute, was permitted to persist. And, because of the private and confidential nature of the proceeding, no one could talk about it. From that point on, I became increasingly concerned about the state of our justice system, which is actively pushing for more, not less, privatization of civil dispute resolution.